"Tarixi Nofeiy" as a source for illuminating the scientific activities of 20th century Bukhara madrasahs (Czech Journal of Multidisciplinary Innovations, 2023)
The memoirs of local historians, foreign tourists and ambassadors are of great importance in the study of the history of Central Asia from the early Middle Ages to the invasion of the Russian Empire. In particular, many sources relating to the political, economic, social and cultural life of the Bukhara Emirate at the beginning of the 20th century have been preserved, they also give a large place to information about the education system. An important source covering the socio-political history of the Bukhara Emirate in the late 19th - early 20th centuries events in the typical manner of a historian, without regard to the interests of the Emirate of Bukhara or the Soviet government. This book was written by historians Sh. Vakhidov and Z. Choriyev. It was translated from Tajik into Uzbek and handed over to the readers. This work consists of an introduction, 15 chapters and a conclusion and was written between 1923 and 1927. This article describes the history of the madrasah of Bukhara at the beginning of the 20th century based on the work "Tarixi Nofeiy".